Analysis of the Socio-Economic Impact of the Presence of Street Vendors: Analisis Dampak Sosial Ekonomi Keberadaan Pedagang Kaki Lima - Putri, Lusia Sari Yudi; Choiriyah, Ilmi Usrotin (Universitas Muhammadiyah Sidoarjo, 2021)
Street vendors in the Gading Fajar housing area are increasingly crowded, making the atmosphere of Sidoarjo Regency increasingly narrow and hot. Taking into account these conditions, the Sidoarjo Government has taken action in the form of temporary transfers for street vendors which are expected to overcome these problems. This study aims to describe the implementation of street vendors' policies in Sidoarjo Regency. This research is a qualitative descriptive study using purposive sampling technique in determining informants. The economic impact of the presence of street vendors in the Gading Fajar Residential Area in terms of income, the majority decreased by almost 50% if selling on weekdays for street vendors in the field. In terms of business development, because the location has not been designated as a relocation location by the government, the empowerment of the Gading Fajar street vendors is still not possible. Meanwhile, in terms of business capital, the government has also not been able to provide assistance or loan recommendations to street vendors who need additional capital for businesses or wholesalers because they are still considered as illegal street vendors.